2018
DOI: 10.1149/2.0151809jes
|View full text |Cite
|
Sign up to set email alerts
|

Actualizing In Situ X-ray Absorption Spectroscopy Characterization of PEMFC-Cycled Pt-Electrodes

Abstract: The family of the PtM (M represents transition metals such as Co, Ni, Pd, etc.) alloys is the most promising cathode electrocatalysts for proton exchange membrane fuel cells (PEMFCs) owing to their superior oxygen reduction reaction (ORR) activity to pure Pt. However, the activity gain fades with long-term PEMFC operation, and the degradation mechanism is not yet fully understood. To truly understand the degradation mechanism of the carbon supported PtM nanoparticles (PtM/C) in the cathode of a membrane electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…S8, Table S2, ESI†). 23 Also, the intensity of Pt–Pt bond (black dashed line) in PtCoRu/C was lower than that of PtRu/C, suggesting a reduced coordination number of Pt owing to the formation of the PtCo alloy (Table S2, ESI†). 24 After the thermal annealing, the Pt–O bond in the PtCo–RuO 2 /C at near 1.5 Å was newly formed, while the Pt–RuO 2 /C had negligible peaks from Pt–O at the same region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S8, Table S2, ESI†). 23 Also, the intensity of Pt–Pt bond (black dashed line) in PtCoRu/C was lower than that of PtRu/C, suggesting a reduced coordination number of Pt owing to the formation of the PtCo alloy (Table S2, ESI†). 24 After the thermal annealing, the Pt–O bond in the PtCo–RuO 2 /C at near 1.5 Å was newly formed, while the Pt–RuO 2 /C had negligible peaks from Pt–O at the same region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the high white line intensity of the Co K-edge (around 1.8) could be identified as the feature of Co 2+ inorganic salt. 56,57 The transformation of Co oxide or the Co 2+ salt (in this research, it was analyzed as CoSO 4 according to the experimental condition and LCA analysis) in MEA was reported to have unfavored the cell performance, 58 which was suggested as another factor that influenced the performance of the MEA. In addition, the results also indicate less Co oxide generation on CS nanostructure.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…In their XAS studies, Hwang et al 59 suggested that the observed minor fraction of surface Co oxide species is very unstable in an acidic environment and immediately dissolves from the particle surface, resulting in a Pt-rich skin. In another in situ XAS study by Miller et al, 60 redeposited CoO was detected in the MEA membrane as a product of catalyst degradation/dissolution during electrochemical cycling. Wang et al discussed the presence of FeO x C y and CoO as an unfavored and ORR activity-reducing species for PtM 3 (M = Ni, Fe, and Co) nanoparticles characterized by the scanning transmission electron microscopy-electron energy loss spectroscopy technique.…”
Section: Introductionmentioning
confidence: 89%
“…In another in situ XAS study by Miller et al . , redeposited CoO was detected in the MEA membrane as a product of catalyst degradation/dissolution during electrochemical cycling. Wang et al discussed the presence of FeO x C y and CoO as an unfavored and ORR activity-reducing species for PtM 3 (M = Ni, Fe, and Co) nanoparticles characterized by the scanning transmission electron microscopy-electron energy loss spectroscopy technique .…”
Section: Introductionmentioning
confidence: 99%